Community policing and intelligence-led policing: An examination of convergent or discriminant validity. Issue 1 (13th December 2018) - Carter, Jeremy G.; Fox, Bryanna
Abstract : Purpose: Despite increased scholarly inquiry regarding intelligence-led policing (ILP) and popularity among law enforcement agencies around the globe, ambiguity remains regarding the conceptual foundation and appropriate measurement of ILP. Although most scholars agree that ILP is indeed a unique policing philosophy, there is less consensus regarding the relationship between ILP and the ever-present model of community-oriented policing (COP). Consequently, there is a clear need to study the empirical distinctions and overlaps in these policing philosophies as implemented by US law enforcement agencies. The paper aims to discuss these issues. Design/methodology/approach: Data were gleaned from the 2007 LEMAS and 2009 NIJ Intelligence surveys. A total of 227 unique police agencies in the USA are included. A series of bivariate, exploratory factor analyses and structural models are used to determine discriminatory or convergent validity across COP and ILP constructs. Findings: The goal was to answer the question: are these two policing philosophies are being implemented as separate and distinct strategies? Results of our exploratory and structural models indicate that COP and ILP loaded on unique latent constructs. This affirms the results of the bivariate correlations, and indicates that COP and ILP have discriminant measurement validity. In other words, COP and ILP are conceptually distinct, even when implemented in police departments across the USA. Implications of these findings and suggestions for future research are discussed. Originality/value: This is the first study to empirically test the discriminant or convergent validity of COP and ILP.